Effect of treatment with original or biosimilar adalimumab on SARS-CoV2 vaccination antibody titers - Dokoupilová, Eva; Vetchý, David; Pavloková, Sylvie; Hanuštiaková, Markéta (International journal of pharmaceutics: X, 2024)
The technological process of production of biosimilars determines the degree of biosimilarity to the original biological drug. In particular, the focus is on the similarity of immunogenic responses. The primary endpoint of our retrospective study was to find the differences in SARS-CoV-2 antibody amount between patients treated with original adalimumab and biosimilar adalimumab MSB11022 (Idacio) and the differences in the SARS-CoV-2 antibody amount between patients treated with and without biological treatment. We collected the gender, autoimmune disease type, age, and treatment data of the patients in the outpatient clinic MEDICAL PLUS, s.r.o., Uherske Hradiste. These patients suffer from autoimmune rheumatic diseases. All patients received the mRNA vaccine (Pfizer/BioNTech - BNT162b2), with a 21-day (interquartile range, 21-24) gap between the two vaccinations. Patients receiving adalimumab were able to develop cellular immune responses after the second vaccination dose, as well as the individuals without adalimumab. In the period of 6-23 weeks after the second vaccination dose (D63 - D182), the SARS-CoV-2 antibody levels did not change significantly in the patients receiving the original adalimumab, while in the patients receiving biosimilar adalimumab a significant decrease was revealed. A statistically significant difference in the SARS-CoV-2 antibody amount between the patients without biological treatment (median: 504.3 U/mL) and with biological treatment (Original and Biosimilar - median: 47.2 and 28.2 U/mL, respectively) was confirmed on day 182. According to our observation, the effect of the treatment type on the increase/decrease of antibodies over time is dominant, while the impact of other variables (gender, methotrexate treatment, autoimmune disease type, and age) was confirmed as insignificant or minor.
Keywords: Adalimumab; Nonparametric statistics; Original; Autoimmune disease; SARS-CoV-2; Biosimilar